“Leaving no one behind”: COVID-19 Response in Black Canadian Communities - Etowa, Josephine; Kohoun, Bagnini; Etowa, Egbe B.; Kiros, Getachew; Mbagwu, Ikenna; Muray, Mwali; Dabone, Charles; Ubangha, Lovelyn; Nare, Hilary (Witness: The Canadian Journal of Critical Nursing Discourse, 2020)
Despite the universal healthcare system in Canada, Canadians of African Descent (CAD) still face numerous problems that place them at higher risk to pandemics such as COVID-19. From the struggles of working as frontline workers, to challenges compounded by pre-existing chronic medical conditions such as Diabetes, CAD may face unique issues, further weighing on their existing and potential health outcomes. This situation calls for closer attention to the specific needs of CAD who may be at greater risk of late diagnosis and delayed treatment for COVID-19. Historically, marginalized communities such as CAD must be included in healthcare considerations and planning, so as to avoid further leaving them behind during and after the storm. Past evidence has shown that structural inequities shape who is affected by disease and its economic fallout. Therefore, the unique needs of CAD must be considered in healthcare planning with the ongoing COVID-19 response. Keywords: pandemic, marginalized, healthcare, COVID-19, Canadians of African Descent